Semi-analytical solutions for the Poiseuille–Couette flow of a generalised Phan-Thien–Tanner fluid - Ribau, Ângela M. (2020)
PTDC/EMS-ENE/3362/2014 POCI-01-0145-FEDER-016665 SFRH/BPD/100353/2014 UID/MAT/00297/2019